Study of herbal vegetation cover in Mazar Chikh Ali – Forest (Jableh - Latakia) - شيخ محمد, ياسين; صقر, نوار (Latakia University Journal -Biological Sciences Series, 2021)
This research was carried out in Lattakia Governorate - Syria during the period 2015-2016, with the aim of identifying the plant species that form the herbaceous vegetation cover in the forest of Mazar Sheikh Ali (Jableh - Lattakia), identifying them and recording their presence, as three sites were selected from the forest. Estimation of vegetation coverage and relative coverage, and the square method was adopted in estimating density and frequency. Plant samples were collected from the forest and dried and then classified according to the available flora. The results of the research showed the presence of 54 species belonging to 53 genera distributed into 18 species. It was widespread in the study area, and the granular arzilla plant occupied Oryzopsis holciformis (M.B) Hack. the highest relative importance (27.89%), followed by clay Inula Viscosa Aiton. (26.67%), then barley Hordium morinum L. (17.71%), and the first site was distinguished by the highest values ​​in terms of quality richness and relative abundance. Plant species in the study area.